The control of syphilis, a contemporary problem: a historical perspective. Issue 3 (1st June 2001) - Green, T; Talbot, M D; Morton, R S
Abstract : The control of syphilis in the United Kingdom and United States has been managed in different ways in each country over the course of the last century. Older more established measures including contact tracing, serological surveillance, and health education strategies together with effective antibiotic therapy have had some success. However, changing social structures on both sides of the Atlantic Ocean have brought newer mathematical and epidemiological methods to the fore. This review looks at the past management of syphilis control in the United Kingdom and United States, and speculates on future prospects for disease management in these countries.